IMPLEMENTASI, FUNGSI MASJID PARIPURNA - Zaili Rusli, Vinni Helvionita, Meyzi Heriyanto, (Jurnal Ilmu Administrasi Negara, 2019)
Implementation, Function of the Plenary Mosque. This study aims to determine and analyze the implementation of the function of the Plenary Mosque Level District in Pekanbaru City and its supporting and inhibiting factors. This research method uses descriptive qualitative method. The research informants were Vice Mayor Pekanbaru, Kabag Kesra, Chairman of the Board of Trustees, Staff, Chairperson of the Mosque and Jamaah. Data collection techniques carried out by interview, observation, and documentation. The results showed that the Pekanbaru City Regulation Number 2 Year 2016 regarding the implementation of the Function of the Plenary Mosque at the District level in Pekanbaru City had not been implemented optimally. This is seen based on the behavioral elements of program implementers who are not aware of their duties to realize the functions of the Plenary Mosque in the fields of idarah, imarah, and ria’ayah.